Cardioprotective Properties of Aerobic and Resistance Training Against Myocardial Infarction - Barboza, C. A.; Souza, G. I. H.; Oliveira, J. C. M. F.; Silva, L. M.; Mostarda, C. T.; Dourado, P. M. M.; Oyama, L. M.; Lira, F. S.; Irigoyen, M.C.; Rodrigues, B. (International Journal of Sports Medicine, 2016)
We evaluated the effects of aerobic and resistance exercise training on ventricular morphometry and function, physical capacity, autonomic function, as well as on ventricular inflammatory status in trained rats prior to myocardial infarction. Male Wistar rats were divided into the following groups: sedentary+Sham, sedentary+myocardial infarction, aerobic trained+myocardial infarction, and resistance trained+myocardial infarction. Sham and myocardial infarction were performed after training periods. In the days following the surgeries, evaluations were performed. Aerobic training prevents aerobic (to a greater extent) and resistance capacity impairments, ventricular dysfunction, baroreflex sensitivity and autonomic disorders (vagal tonus decrease and sympathetic tonus increase) triggered by myocardial infarction. Resistance training was able to prevent negative changes to aerobic and resistance capacity (to a greater extent) but not to ventricular dysfunction, and it prevented cardiovascular sympathetic increments. Additionally, both types of training reduced left ventricle inflammatory cytokine concentration. Our results suggest that aerobic and, for the first time, dynamic resistance training were able to reduce sympathetic tonus to the heart and vessels, as well as preventing the increase in pro-inflammatory cytokine concentrations in the left ventricle of trained groups. These data emphasizes the positive effects of aerobic and dynamic resistance training on the prevention of the negative changes triggered by myocardial infarction.
Keywords: aerobic exercise training; resistance exercise training; myocardial infarction; ventricular function; autonomic function; inflammation